2009
DOI: 10.1007/s00213-009-1573-9
|View full text |Cite
|
Sign up to set email alerts
|

Neural representation of reward in recovered depressed patients

Abstract: Introduction Anhedonia, a loss of interest and pleasure in normally rewarding stimuli, is a key diagnostic criterion for major depression. It has been suggested that deficits in the processing of reward-relevant stimuli could represent an endophenotype for depression. We hypothesized that people at risk of depression by virtue of a personal history of the illness would show impaired neural responses to a primary rewarding stimulus. Materials and methods Using functional magnetic resonance imaging, we measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
214
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(243 citation statements)
references
References 46 publications
(60 reference statements)
26
214
2
1
Order By: Relevance
“…From a neuroscience perspective, there is evidence that clinically depressed, recovered depressed, and individuals at risk for depression show abnormal neural functioning during both reward anticipation and outcome phases (e.g., Forbes et al, 2009;Gotlib et al, 2010;Knutson et al, 2008;McCabe et al, 2009;Pizzagalli, Holmes, et al, 2009;Smoski et al, 2009;Steele et al, 2007). However, reward anticipation in relation with differences in incentive salience and dopamine functioning seems to be of particular importance (Berridge, 2007;Dichter, 2010;Nestler & Carlezon, 2006;Sherdell et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a neuroscience perspective, there is evidence that clinically depressed, recovered depressed, and individuals at risk for depression show abnormal neural functioning during both reward anticipation and outcome phases (e.g., Forbes et al, 2009;Gotlib et al, 2010;Knutson et al, 2008;McCabe et al, 2009;Pizzagalli, Holmes, et al, 2009;Smoski et al, 2009;Steele et al, 2007). However, reward anticipation in relation with differences in incentive salience and dopamine functioning seems to be of particular importance (Berridge, 2007;Dichter, 2010;Nestler & Carlezon, 2006;Sherdell et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a number of recent studies demonstrated reduced activity in cortical and subcortical components of the neural reward circuit of depressed and dysphoric individuals, both during anticipation and outcome phases of reward processing (e.g., Forbes et al, 2009;Knutson et al, 2008;Pizzagalli, Holmes, et al, 2009;Smoski et al, 2009;Steele, Kumar, & Ebmeier, 2007). Most of these brain imaging studies concerned patients with major depression but also recovered depressed (McCabe, Cowen, & Harmer, 2009) and healthy populations at risk (Gotlib et al, 2010). In a similar vein, there is evidence for electrocortical hypoactivation of left prefrontal areas in depressed and dysphoric individuals-in the resting state but also during reward anticipation (e.g., Davidson, Pizzagalli, Nitschke, & Putnam, 2002;Gotlib, Ranganath, & Rosenfeld, 1998;Harmon-Jones et al, 2002;Shankman, Klein, Tenke, & Bruder, 2007;Thibodeau, Jorgensen, & Kim, 2006;Tomarken & Keener, 1998).…”
Section: Reward Insensitivity In Depression and Dysphoriamentioning
confidence: 99%
“…However, their role has not been fully understood. To date, a couple of studies have demonstrated associations between depression and reduced neural responses during the viewing of pleasant facial expressions and words (Epstein et al, 2006;Monk et al, 2008;Surguladze et al, 2005) and during the sight and taste of pleasant chocolate stimuli (McCabe et al, 2009;McCabe et al, 2012). These findings point to the general nature of reduced reward responsiveness in depression, beyond monetary rewards.…”
Section: Social Rewards In Depressionmentioning
confidence: 97%
“…It is possible to conceive of a vicious cycle where impaired social reward responsiveness leads to even less social reinforcement from the environment and to even higher depression, and vice versa (Beck et al, 1979). Studies on remitted depressed patients and on high-risk populations suggest that reduced reward responsiveness might have trait-like character (Gotlib et al, 2010;McCabe et al, 2009;McCabe et al, 2012). Nevertheless, future studies using prospective longitudinal designs are needed to answer these questions.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…In humans, mesolimbic activity and DA neurotransmission in the NAc are robustly engaged during the anticipation of a number of salient cues regardless of valence (Knutson et al, 2000;Scott et al, 2006;Scott et al, 2007b;McCabe et al, 2009;Spreckelmeyer et al, 2009). However, a potential role of BDNF on the processing of salient cues of different valences as it relates to DA neurotransmission has not been studied in humans.…”
Section: Introductionmentioning
confidence: 99%